KEGIATAN PEMBELAJARAN BERTANI PADA SISWA TUNANETRA DI SLB AGRO INDUSTRI CISARUA KABUPATEN BANDUNG BARAT - Ariyanti, Ira; Sunanto, Juang; Nawawi, Ahmad (PEDAGOGIA, 2017)
This study examines the learning activities farming in the blind students in SLB Agro Industry. This study aims to describe the learning activities farming in the blind students in SLB Agro Industries Cisarua, West Bandung regency. Descriptive research methods - qualitative. Data was collected through interviews, observation, and documentation with triangulation techniques. Analysis of the data by reduction, display, conclusions, and verification. Research subjects in this study consisted of principals, teachers, students, and parents. The results of this study indicate that outlines the vision; mission SLB Agro Industry stressed the independence of the learners to adapt to the environment. Then curriculum applied that functional curriculum, while the agricultural curriculum refers to the agriculture vocational curriculum tailored to the needs and abilities of learners. Human resources involved in the eight-man special education teachers certified S1, some experts manager learning programs are also certified S1 farming and some citizens. Responses learners on learning activities have been fun, though the lack of theory given constraints. The response of parents can be quite good because it is often involved in school activities. The neighborhood around the school or community support and engage in activities in the SLB Agro Industries, even there are also some of this Agreement.